(3TQM eNJUQ GdbOhQj aj Gdabgs - (3GdCbWY, CMeO Hf eMeO Hf eMeO, J (B474 (3g`s
(3ChdgG (B:s
(3dHSg hGdeTbI JdMb HfRYg cGdNa bjd dg GdeTbI EfeG JYJHQ aj GdZGdH hGdLhQH dG jdHS ZGdHG hdG jJCJi ehGUdI GdeTj ajgs
(3BNQgG (B:s
(3ajeG gh TQjc ajg dG jUM hdG jLH dg CLQ dCf GdYed hbY dfaSg hEPG de jUM GdYbO cGf GdNGQL HjfgeG Ydi bOQ Gdedcjf dCfg feG edcgeGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 213s
(3eYLe GdeDdajf (B1 / 291s
(3cTa GdXfhf (B2 / 1631s
(3GdLhGgQ GdeVjI (B1 / 119s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs